(untitled) (Baghdad Science Journal, 2011)
In this work a flowsheet has been put for the recovery of uranium and plutonium from 2.5M nitric acid solutions using 17.5% tributyl phosphate (TBP) and 2.5% trioctylamine (TOA) in kerosene diluent . The fission products (resulting from irradiated of uranium samples in nuclear research reactor) were removed from the desired actinides U & Pu .The organic phase TBP/TOA/Kerosene, containing both actinides U&Pu were stripped using 0.1 M HNO3. Trioctylamine (2.5 volume ratio ) in mesitylene , has been used in conditions appropriate for the recovery of Pu . From the experiments done using mixer- settler , the concentration of uranium in the organic phase in such conditions was very low ,not exceeding parts of a million .